FRAKSINASI AMILASE DARI Endomycopsis fibuligera ITBRcc64 DENGAN METODE PRESIPITASI AMONIUM SULFAT - Afaf Baktir (The East Java Biological Society, 1995)
Endomycopsis fibuligera ITB.R.cc.64 produced high extracellular amylase activity. It showed two kinds of amylase activities, those are liquefication and saccharification. The aim of this research are to separate each kind of amylase by fractionation with ammonium sulfate and to test the specific activity of each fraction. It was done three fraction ammonium sulfate: 0-40 %, 40-60 %, and 60-80%. This fraction has the strong liquefication activity of 20.847 U/mg protein, the second fraction has the strong saccharification activity of 18.903 U.mg protein and the weak liquefication activity of 1.756 U/mg protein.